Enhanced secretion of promyogenic exosomes by quiescent muscle cells - Devan, Prabhavathy; Ghosh, Ananga; Rao T., Pallavi; Raychaudhuri, Swasti; Adicherla, Harikrishna; Devanshi, Himadri; Kshetrapal, Pallavi; Dhawan, Jyotsna (Frontiers in Cell and Developmental Biology, 2024)
Signaling interactions are important during skeletal muscle regeneration, where muscle cells in distinct states (quiescent, reactivated, proliferating and differentiated) must coordinate their response to injury. Here, we probed the role of secreted small extracellular vesicles (sEV/exosomes) using a culture model of physiologically relevant cell states seen in muscle regeneration. Unexpectedly, G0 myoblasts exhibited enhanced secretion of sEV ( 150 nm) displaying exosome markers (Alix, TSG101, flotillin-1, CD9), and increased expression of Kibra, a regulator of exosome biogenesis. Perturbation of Kibra levels confirmed a role in controlling sEV secretion rates. Purified sEVs displayed a common exosome marker-enriched proteome in all muscle cell states, as well as state-specific proteins. Exosomes derived from G0 cells showed an antioxidant signature, and were most strongly internalized by differentiated myotubes. Functionally, donor exosomes from all muscle cell states could activate an integrated Wnt reporter in target cells, but only G0-derived exosomes could induce myogenic differentiation in proliferating cells. Taken together, we provide evidence that quiescence in muscle cells is accompanied by enhanced secretion of exosomes with distinct uptake, cargo and signal activating features. Our study suggests the novel possibility that quiescent muscle stem cells in vivo may play a previously under-appreciated signaling role during muscle homeostasis. (199)